Determining Consumers’ Willingness to Buy Halal Meat - Firdausi, Asri Sekar Mawar; Farahdiba, Dea; Munthe, Abdillah Menri (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2020)
The halal food industry is no longer underrated. Since consumers became very concerned about their daily consumption considering the hygiene that should be maintained. This research was aimed to measure the Indonesian consumers’ willingness to buy halal food, especially meat products, based on trust, awareness, packaging information, and food safety. However, Indonesian consumers’ demand for halal food is not proportional comparing to a large number of the Muslim population. Contrast to previous similar studies that adopting the Theory of Planned Behavior (TPB) or Theory of Reasoned Action (TRA) that focused more on halal awareness and halal labels, this study was adopting Hedonic Theory. This research using 186 data that were collected by online questionnaires. Data then analyzed using multiple linear regression and Ordinal Least Square (OLS). Results showed that only halal awareness and food safety are proven to have significant positive effects on willingness to buy. Regardless of Muslim and non-Muslim, halal awareness and food safety attract consumers’ willingness to buy halal-labeled meat products. To increase the willingness to buy halal meat products in Indonesia, the government and producers must be able to encourage awareness of the importance of eating halal food. Furthermore, they also must ensure the safety of that food. Hopefully, these findings can become input for stakeholders.